Integrated Management of Verticillium Wilt of Cacao - Bouchon, Anne-Sophie; Hoopen, Gerben Martijn ten (Frontiers in Agronomy, 2022)
The vascular disease Verticillium wilt of cacao (Theobroma cacao), caused by the soilborne fungus Verticillium dahliae, is often qualified as a “minor” disease. However, it can cause severe losses locally, for example, in western Uganda and the Northeast of the Democratic Republic of Congo. This disease is difficult to control, notably due to an extended host range and prolonged survival in the soil. Therefore, Verticillium wilt must be addressed through an integrated disease management strategy as employed for other tree crops such as olive. Few studies, nonetheless, have focused on how to confront this disease in cacao. This paper aims to provide an overview of our knowledge on Verticillium wilt on cacao and the integrated disease management strategies for preventing and controlling it. Promising avenues based on findings in other crops that could be adapted to cacao are also explored. Good agricultural practices, genetic resistance, biological control, induced resistance, and the use of organic amendments with or without biocontrol agents are discussed. Moreover, the potential benefits of some of these solutions toward the resistance to other cacao diseases, abiotic stress, and nutrition improvement are presented.